Indonesian undergraduate students' perceptions of problem-based learning implementation in an ELT class: A small-scale survey - Zalfah Ananda Juver; Willy Prasetya (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2022)
This study aimed at identifying Indonesian undergraduate students’ perceptions of Problem-Based Learning (PBL) implementation in an English language education department at a private university in Indonesia. Using total population sampling, 74 students who were taking a language classroom management course in which PBL was implemented through collaborative work were involved in this survey study.  The data were collected using a 21-item questionnaire from Jaeger and Adair (2014) that was based on Senocak (2009). The data were then analyzed statistically to identify the participating students’ perceptions of PBL implementation by interpreting the patterns of the data. Based on the results of this study, the participants tended to perceive that PBL helped them become more self-directed. However, many of them felt that the collaborative work implemented in PBL was more a difficulty than an ease. The implication of this study is also discussed.DOI: 10.26905/enjourme.v7i2.9032